The desirable donor pig to eliminate all xenoreactive antigens. (2nd March 2019) - Ladowski, Joseph; Martens, Greg; Estrada, Jose; Tector, Matthew; Tector, Joseph
Abstract: The humoral barrier has been the limiting factor in moving xenotransplantation towards the clinic. Improvements in somatic cell nuclear transfer and genome editing, particularly CRISPR‐Cas9, have made it possible to create pigs with multiple glycan xenoantigen deletions for the purposes of reducing xenoreactive antibody binding to the xenografted organ. Recent studies have also considered the aetiology and existence of antibodies directed at the swine leucocyte antigen (SLA) complex, and potential genetic engineering strategies to avoid these antibodies. Evaluation of xenoreactive antibody binding is very important for the advancement of xenotransplantation, because if patients do not have any detectable xenoreactive antibody, then it is reasonable to expect that cellular rejection and not antibody‐mediated rejection (AMR) will be the next hurdle to clinical application.